IQOS point-of-sale marketing strategies at a time of legislation transition in Israel. (30th September 2020) - Bar Zeev, Y; Berg, C; Abroms, L C; Levine, H
Abstract: Background: Heated tobacco products (HTP), such as Philip Morris IQOS, have penetrated the global tobacco market. Currently the only HTP on the market in Israel, IQOS was introduced in 2016. The device is sold in specialty stores and online; while the heat sticks (HEETS) are sold at traditional retailers. In 01/2019 a ban on advertisements in all media (excluding print media) and at the point-of-sale (POS) went into effect. In 01/2020, a POS display ban and plain packaging went into effect. Understanding the POS marketing strategies at a time of regulatory transition could aid regulatory efforts in other countries. Methods: Observations were conducted in 80 retailers carrying HEETS in 4 large Israeli cities in 12/2019, before the POS display ban and plain packaging went into effect. Data were collected using an adapted version of the Standardized Tobacco Assessment for Retail Settings, which assessed store characteristics, product offerings, pricing, promotional strategies, and placement. Results: All retailers sold cigarettes; 51% carried also electronic cigarettes. Only one retailer carried the IQOS device. HEETS packages were visible to customers in 47% of retailers. Over 60% carried at least 3 HEETS different flavours (out of 5 available). In all but one retailer, HEETS were sold at higher prices than cigarettes, on average 21% more expensive. Posted ads were uncommon. In 14.5% of retailers, a special IQOS product display cast was prominent. Additionally, 25% of retailers placed cigarettes and 14% placed HEETS near youth-oriented merchandise. Conclusions: This study provides insights into IQOS marketing strategies during a period of regulatory transition. Findings suggest that IQOS-specific promotions were not common, but a proportion of retailers highlighted IQOS via displays and/or proximity to youth-oriented merchandise. Moreover, IQOS may be promoted to higher socio-economic status populations, as indicated by pricing and possibly by availability of products. Key messages: Understanding IQOS marketing strategies at point-of-sale is critical to inform regulatory measures globally. IQOS marketing strategies in Israel at the point-of-sale suggest that IQOS is promoted to higher socio-economic status populations.